Study on optical properties of novel Ru(II) complex - Vuong, Bui Xuan (Vietnam Journal of Chemistry, 2017)
A novel Ru(II) complex composed of Ruthenium and 3 ligands has been successfully synthesized. The ligands are firstly synthesized ; the ligand 1,10-phenanthroline-5-carboxylic acid (compound D) acts as an anchor for connecting with different compound (for example, connecting with the quantum dots) whereas the 2 other ligands (compound H) playing important role for linear and non-linear optical properties. Secondly, these ligands (compound H, compound D) are attached to initiator Ru salt, respectively. Optical properties of this novel Ru(II) complex were investigated via absorption, luminescent measurements. Additionally, I also used theoritical calculation TDDFT (time dependent density functional theory) to display frontier molecular orbitals of ligands for linear and non-linear optical properties, to assign electronic transitions in absorption spectra of complex. Significant result is luminescence intensity dependent on the dioxygen concentration, ascribed to the luminescence from 3MLCT state, centered at 600 nm. Energy transfer between 3MLCT state and the fundamental triplet state of dioxygen can be studied in order to evaluate the photosensitizing ablities of the complex. This complex can also be used as oxygen concentration sensor at a given temperature. Keywords. Ru(II) complex, ligands, anchor, luminescence, quantum dot